‘SIMDELTA GLOBAL’- TOWARDS A STANDARDISED INTERACTIVE MODEL FOR WATER INFRASTRUCTURE DEVELOPMENT - Ties RIJCKEN; David K. CHRISTOPHER (European Journal of Geography)
The research project ‘SimDelta’ builds on novel internet technology to support the development of the Rhine-Meuse delta water infrastructure. It has three goals: education, organisation of research and design studies, and stakeholder polling. A current question is how the SimDelta technology could be made transferable to systems outside Europe, such as in California, Shanghai, Thailand and Indonesia. Fundamentally, all water systems are similar. Technically they differ in scale, geometry, resolution and functional emphasis, but system boundaries can be standardised. It is essential that SimDelta graphically acknowledges different data quality levels, to allow for standardisation and piecemeal development. Political coordination of infrastructure improvements appears to be difficult everywhere. Since SimDelta aims to clarify connections between high and low scale levels, it is expected to benefit the development of any water system. However, strategically it is recommended to start with the California system, for reasons of scientific maturity and political openness.